Description of clinical cases of the familial form of diabetes mellitus HNF1A-MODY - A. A. Baranova; I. V. Druk; A. K. Ovsyannikova (Лечащий Врач, 2021)
Adult type of diabetes mellitus in young people (MODY) is a group of diseases associated with gene mutations leading to pancreatic β-cell dysfunction. There are 14 known variants of MODY, the most studied are MODY 1-5. The article presents a clinical cases of MODY3 which is based on a mutation of the HNF1A gene.We observed 2 families in which young girls of 26 and 25 years old were probands, respectively. Diabetes mellitus (DM) was first diagnosed in them at the age of 16. At the onset of the disease, a patient from 1 family had complaints of a nonspecific nature, glucosuria, hyperglycemia up to 9 mmol/l, HbA1с – 8%. And in a patient from 2 families, hyperglycemia up to 14 mmol/l was detected by chance, there were no complaints. When examined 10 years after the diagnosis of diabetes in both patients, the level of C-peptide was within the reference values, which indicates the preservation of the secretory function of the pancreas. Antibodies in a patient from 1 family were negative, compared with a patient from 2 families (the presence of antibodies to GAD was detected), the level of HbA1с was 7.8% and 5.9%, respectively. Of the concomitant diseases, 2 probands were diagnosed with autoimmune thyroiditis. Diabetic peripheral polyneuropathy was a complication of diabetes in both patients. A burdened family history of carbohydrate metabolism disorders was observed in 2 families and was followed in 3 maternal generations. Based on the age of diagnosis of diabetes, preserved secretion of β-cells of the pancreas, the absence of antibodies, determination of diabetes in relatives in three generations, it was suggested that the patients had HNF1A-MODY. After a molecular genetic study, the diagnosis was confirmed in the observed patient and her mother (family 1) and in a patient from family 2. These clinical cases demonstrate variants of the course of monogenic diabetes.